2006
DOI: 10.1590/s0100-204x2006000200021
|View full text |Cite
|
Sign up to set email alerts
|

Atividade in vitro do extrato de própolis contra agentes bacterianos da mastite bovina

Abstract: Resumo -Este trabalho foi desenvolvido com o objetivo de avaliar a atividade in vitro do extrato alcoólico de própolis, contra agentes da mastite bovina, comparando-o aos principais antimicrobianos utilizados no tratamento convencional. In vitro activity of propolis extract against bovine mastitis bacterial agentsAbstract -The present study aimed to determine the in vitro activity of propolis extract, comparing it to the most common antibacterial drugs against bovine mastitis bacterial agents. Thirty-six isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
(4 reference statements)
0
3
0
4
Order By: Relevance
“…The results showed that both EPA and EPB showed antimicrobial activity against isolates of Staphylococcus spp., in agreement with previous studies indicated that the antibacterial activity of propolis is more pronounced against Gram-positive bacteria (Langoni et al 1996, Sforcin et al 2000, Pinto et al 2001, Fernandes Júnior et al 2003, Auricchio et al 2006, Trusheva et al 2010, Aguiar et al 2014. The antibacterial activity of the EPA, with 90.9% susceptibility, was similar to the Loguercio et al (2006) and Coelho et al (2010) which showed susceptibility of 94.4% in coagulase-positive Staphylococcus. When comparing the two extracts, it was verified that isolates of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The results showed that both EPA and EPB showed antimicrobial activity against isolates of Staphylococcus spp., in agreement with previous studies indicated that the antibacterial activity of propolis is more pronounced against Gram-positive bacteria (Langoni et al 1996, Sforcin et al 2000, Pinto et al 2001, Fernandes Júnior et al 2003, Auricchio et al 2006, Trusheva et al 2010, Aguiar et al 2014. The antibacterial activity of the EPA, with 90.9% susceptibility, was similar to the Loguercio et al (2006) and Coelho et al (2010) which showed susceptibility of 94.4% in coagulase-positive Staphylococcus. When comparing the two extracts, it was verified that isolates of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 58%
“…In this sense, propolis, a resinous product produced by honey bees, is being used in the treatment of human and animal diseases (Coelho et al 2010) and has been shown to be a viable and quite promising alternative in the treatment of infections caused by S. aureus (Pinto et al 2001, Endler et al 2003, Auricchio et al 2006, Zeighampour et al 2014, Shahbaz et al 2015, Chen et al 2018) due to its proven antibacterial activity (Barbosa et al 2009, Araujo & Marcucci 2011. However the results using propolis are still conflicting (Pinto et al 2001, Loguercio et al 2006), due to its distinct and complex chemical constitution, necessitating the development of further research (Lustosa et al 2008, Rufatto et al 2017). In addition, there are few conclusive results regarding their action against MRSA, that play an important role in nosocomial infections (Taubes 2008) and a serious problem on a global scale (Astani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstram que a alta prevalência da mastite pode estar associada às más condições de higiene do ordenhador, bem como dos tetos e úberes das vacas antes, durante e após a ordenha (Oliveira et al, 2009 As cepas de S. aureus resistentes a diferentes grupos de antibióticos usados no combate da mastite bovina, muitas vezes estão relacionadas à má utilização de determinado produto, como, por exemplo, aplicação em subdosagens, período insuficiente de tratamento dos animais (Araújo, 1998;Fontana et al, 2010 (Loguercio et al, 2006).…”
Section: Resultsunclassified
“…Variações são descritas no poder antimicrobiano da própolis frente a bactérias Gram positivas e Gram negativas (vargas et al, 2004;loguErCio et al, 2006 (dE vECChi;drago, 2007). Esses resultados divergentes podem estar relacionados à diferença da flora e clima entre Brasil (tropical ou subtropical) e Egito (temperado) (orsi et al, 2007;kujumgiEv et al, 1999).…”
Section: Discussionunclassified